(untitled) - Viers, Jérôme (Comptes Rendus. Géoscience, 2025)
The objective of this work is to make an inventory of copper isotope signatures (what amplitudes? what signs?) in the main reservoirs (rock, soil, river, oceans). After almost 25 years of work carried out with precise measurements of these isotopic ratios, it is important to consider whether they can provide us useful constraints in the understanding of the cycle of large-scale elements. The goal is not to discuss all the hypotheses of each paper, of each site, but to present the compilation of data in a neutral way and identify the significant features. This work should provide a simple, hard-hitting overview of the potential of this isotopic tool as a source tracer, but also of the main mechanisms at play within and between reservoirs.